Evaluation of fisheries inspection and quarantine service in the Philippines - Javier, Edwin C B. (Miagao, Iloilo University of the Philippines in the Visayas, 2001)
The study was conducted to evaluate the implementation of the Fisheries Inspection and Qaurantine Service (FIQS) in the Philippines after it was strenghtened through Republic Act No. 8550 in 1998. Eight major fishing regions were investigated namely Regions III (Pampanga), NCR/ Region IV (Metro Manila), VI (Iloilo), VII (Cebu), IX (Zambianga), X (Cagayan de Oro), XI (Davao) and XII (Cotabato) to determine the performance of FIQS in each region in terms of Manpower and Support Facilities, Domestic and International Fishery Product Movements, and Average Number of Foreign Sea/Aircarft Incoming/Outgoing (per month). Data were gathered and recorded via a data checklist. Results of the study show the inadequacy of the current FIQS in the country. Constraints in mapower, personnel training and development, physical facilities such as laboratories and analysis equipment, administrative procedure, networking with other industry-related agencies and communications hinder the development and implementation of FIQS. Unless these concerns are resolved, the Philippine fishing sector will have a difficult time enhancing its bid for competitiveness in the international seafood market.
Special Problem (MMA) -- Miagao, Iloilo : University of the Philippines in the Visayas, 2001.